2012
DOI: 10.1021/es3037737
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Methane in CO2 Transport and Storage for CCS Technology

Abstract: CO(2) Capture and Storage (CCS) is a good strategy to mitigate levels of atmospheric greenhouse gases. The type and quantity of impurities influence the properties and behavior of the anthropogenic CO(2), and so must be considered in the design and operation of CCS technology facilities. Their study is necessary for CO(2) transport and storage, and to develop theoretical models for specific engineering applications to CCS technology. In this work we determined the influence of CH(4), an important impurity of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 21 publications
2
58
0
Order By: Relevance
“…A variety of compositions may be present in the gas stream due to the presence of trace contaminants remaining after the CO2 capture process. Methane, for example, can be present as an impurity in the injection gas (Blanco et al, 2012;Mohd Amin et al, 2014). Methane can also be present as a native gas within the reservoir (Taggart, 2010;Oldenburg and Doughty, 2011;Hosseini et al, 2012), or could be produced through methanogenesis either in the reservoir or after CO2 enters the aquifer (Leu et al, 2011).…”
Section: Other Aquifersmentioning
confidence: 99%
“…A variety of compositions may be present in the gas stream due to the presence of trace contaminants remaining after the CO2 capture process. Methane, for example, can be present as an impurity in the injection gas (Blanco et al, 2012;Mohd Amin et al, 2014). Methane can also be present as a native gas within the reservoir (Taggart, 2010;Oldenburg and Doughty, 2011;Hosseini et al, 2012), or could be produced through methanogenesis either in the reservoir or after CO2 enters the aquifer (Leu et al, 2011).…”
Section: Other Aquifersmentioning
confidence: 99%
“…Future studies should investigate the effect of these greater concentrations of CH 4 in the gas mixture on pH. While 10% may be an overestimate of CH 4 present in CO 2 sequestration projects, Blanco et al (2012) stated that industrial emissions can reach CH 4 concentrations of >5%. The Eh measured in the columns with and without CH 4 were similar at the beginning of the experiments.…”
Section: Ph and Ehmentioning
confidence: 99%
“…Blanco et al (2012) reported CH 4 levels as high as 6% in industrial emissions in Spain (generated by waste management); however, a study conducted by de Visser et al (2008), in agreement with the European Enhanced Capture (ENCAP) project, suggested a limit of 4% CH 4 in gas injection streams. CH 4 can also be present as a native gas prior to injection (Taggart, 2010;Oldenburg and Doughty, 2011;Hosseini et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations